Maternal Mortality and Near Misses in the Spectrum of Hypertensive Disorders in Pregnancy at Dr. Kariadi Hospital in 2024 - Purba, Danias Eduward; Cahyanti, Ratnasari Dwi (Medica Hospitalia : Journal of Clinical Medicine, 2026)
BACKGROUND: High maternal mortality from hypertension in pregnancy reflects poor early detection and management. Preeclampsia-eclampsia remains a major cause of severe outcomes. AIMS:  To analyze the relationship between spectrum of hypertensive disorders in pregnancy and maternal near misses and mortality at Dr. Kariadi Hospital in 2024. METHOD: Cross-sectional study using medical records of pregnant women with hypertensive disorders. All cases were analyzed to assess the relationship between spectrum of hypertension  and maternal near miss and maternal death using the chi-square test, in accordance with the ethical approval of KEPK Dr. Kariadi Hospital. RESULT:  Most pregnant women had preeclampsia/eclampsia (77.3%), followed by superimposed preeclampsia (14.2%). Maternal near miss occurred in 13.3% and mortality in 9.3% of cases, with 206 live births. Organ dysfunction was found in 22.7%, mainly cardiovascular (10.7%), followed by respiratory, coagulation (each 2.2%), and immunological (5.8%). Overall organ dysfunction, especially cardiovascular, respiratory, renal, and coagulation associate with maternal near miss (p<0.05). The highest risks were seen in cardiovascular (PR 19.54; CI95% 10.13-37.66), renal (PR 7.96; CI95% 5.63-11.26), respiratory (PR 6.76; CI95% 3.83-11.94), and coagulation dysfunction (PR 4.88; CI95% 2.20-10.86). Immunological dysfunction was strongly associated with maternal mortality and had the highest risk (PR 26.50; CI95% 13.42-52.29). CONCLUSION: Preeclampsia/eclampsia is the dominant condition and correlates to maternal near miss and death. Organ dysfunction significantly worsens outcomes.